Comparative microbiological and phytochemical study of extracts from leaves of varietal forms of the genus Mentha L. - M. A. Kazakova; V. A. Kurkin; V. M. Ryzhov; A. V. Lyamin; A. V. Kozlov (Разработка и регистрация лекарственных средств, 2025)
Introduction. Due to the increasing resistance to antimicrobial drugs of different spectrum of action in the population, the issue of searching for new drugs with antimicrobial activity is currently the most relevant. Peppermint (Mentha piperita L.) is known for its medicinal properties, which are due to the presence of many biologically active compounds in the medicinal plant. The composition of extracts from the leaves of peppermint includes essential oil, the main component of which is menthol, as well as non-volatile phenolic compounds – flavonoids (luteolin etc.) and phenylpropanoids (rosemary acid, salvianolic acid, chlorogenic acid etc.).Aim. To screen and compare the antimicrobial activity of aqueous-alcoholic extracts from peppermint leaves and mint varieties and to perform comparative qualitative analysis by high performance liquid chromatography (HPLC).Materials and methods. The objects of the study were aqueous-alcoholic extracts on 70 % ethyl alcohol obtained by fractional percolation method from leaves of varieties of peppermint (Mentha L.) and alcoholic solutions of standard samples of luteolin and menthol. The minimum inhibitory concentration was determined by double serial dilutions in Mueller – Hinton nutrient broth (Bio-Rad, USA). Bacillus cereus (ATCC 29213) Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853), Candida albicans (ATCC 90028) strains were used as test cultures. Chromatographic analysis was carried out by HPLC on a Milichrome-6 microcolumn liquid chromatograph (NPASC "Nauchpribor") under the following conditions: gradient mode, steel column KAX-6-80-4 (No. 2; 2 × 80 mm; Separon-C18, 7 μm), eluent system: acetonitrile (PFA) – 1 % acetic acid (PFB) solution (1 : 9; 2 : 8; 3 : 7; 8 : 2), elution rate – 100 μl/min, eluent volume – 2500 μl. The substances were detected at a wavelength of 330 nm. The volumes of injected samples were 2 μl.Results and discussion. In the course of the study it was found that all the tested samples give a stable prevailing antimicrobial effect against the strains of test cultures.Conclusion. The data obtained in the course of the conducted study indicate the prospect of obtaining medicinal herbal preparations based on mint leaves of different species and varieties, showing antimicrobial activity, and their introduction into medical and pharmaceutical practice.